Implementasi Pendayagunaan Zakat Produktif Terhadap Pemberdayaan Mustahiq Pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Lumajang - Indra Hidayatullah (JES (Jurnal Ekonomi Syariah), 2019)
Zakat can be utilized for productive efforts in the context of handling the poor and improving the quality of the people. Along with Allah’s commands to Muslims to pay zakat, zakat is one of the pillars of Islam which is not only of a vertical dimension, but also horizontal aspect. Zakat is an important worship in anticipating social inequality in its implementation. It is still largely traditional and does not pay attention to the welfare of the people, in fact the development of muslims is the majority population of this nation and it has a huge potential to be used as a source of funds from zakat. The result of research shows that utilization of productive zakat in the National Amil Zakat Agency (BAZNAS) of Lumajang Regency is to make people stand alone so that they can improve their standard of living and so as not to always depend on zakat funds. Mustah}iq empowerment in the National Amil Zakat Agency (BAZNAS) Lumajang Regency is by running a productive zakat system for business capital assistance for the mustah}iq and consumptive zakat system. Utilization of productive zakat funds is one of the processes carried out by the Lumajang National Amil Zakat Board (BAZNAS) to make the mustah}iq be independent so that they can improve their standard of living and become muzakki> as has become the vision of the National Amil Zakat Agency (BAZNAS) Regency Lumajang. The form of zakat fund utilization towards mustah}iq empowerment at the National Amil Zakat Board (BAZNAS) of Lumajang Regency is divided into two empowerments, namely consumptive and productive empowerment. Consumptive empowerment is the provision of funds that can be directly consumed by mustah}iq. While productive is the provision of capital in increasing business. Both in the form of funds and gifts in the form of work tools. The most effective thing in empowering the mustah}iq is empowering by using productive zakat funds which have benefited a lot of mustah}iq. Empowerment of zakat funds in relation is to convey part of the assets owned to a group called eight asnaf, namely the poor, poor, ‘a>mil or administrators of zakat, muallaf, riqa>b (slaves), gha>rimi>n, fi> sabi>lilla>h and Ibn Sabi>l. Keywords: Implementation, Utilization, Productive zakat, Mustah}iq